Role of MAIT cells in pulmonary bacterial infection. (September 2018) - Hartmann, Nadine; Harriff, Melanie J.; McMurtrey, Curtis P.; Hildebrand, William H.; Lewinsohn, David M.; Kronenberg, Mitchell
Highlights: Activated MAIT cells accumulate in infected tissues and provide protection against various pulmonary bacterial infections. Synthesis of MAIT cell antigen is decreased in the presence of riboflavin. Clinical Streptococcus pneumoniae isolates differ greatly in their content of activating antigens for MAIT cells. Abstract: Mucosal-associated invariant T (MAIT) cells represent a population of innate T cells that is highly abundant in humans. MAIT cells recognize metabolites of the microbial vitamin B pathway that are presented by the major histocompatibility complex (MHC) class I-related protein MR1. Upon bacterial infection, activated MAIT cells produce diverse cytokines and cytotoxic effector molecules and accumulate at the site of infection, thus, MAIT cells have been shown to be protective against various bacterial infections. Here, we summarize the current knowledge of the role of MAIT cells in bacterial pulmonary infection models.